Manufacture of an ether-modified copolyester fiber with high physical performances and its applying feasibility for copper clad laminate (CCL) substrate of fifth generation long-term evolution (5 G LTE) - Yun-Ping Chang; Syang-Peng Rwei; Meng-Hsin Chen; Lung-Chang Liu (Next Materials)
Although L-Glass is a competent reinforced fiber for the copper clad laminate (CCL) substrate of fifth generation long-term evolution (5 G LTE), its high-cost and intricate manufacturing procedure consumes much energy and time, leading to high carbon emission. To solve this issue, an ether-modified copolyester fiber with high tensile strength of 1863 MPa, excellent elastic modulus of 54 GPa, low density of 1.4 g/cm3, moderate coefficient of thermal expansion (CTE) of 5.1 ppm/°C, and good thermal conductivity of 1.63 W/m*K has been firstly prepared by the proper formula, melt-spinning apparatus, and thermal treatment. With lab-made melt-spinning copolyester fiber, low-dielectric-property epoxy resin, and the copper foil, moreover, we have also fabricated the CCL substrate prototype of 5 G LTE by the dry-laid process, impregnation, and hot compression, evaluating the feasibility because its Dk (10/28 GHz), Df (10/28 GHz), peel strength to copper foil, and CTE can reach 3.04/3.02, 0.0031/0.0041, 84.6 N/cm, and 25.6 ppm/°C, respectively. Experimental results indicate that lab-made melt-spinning copolyester fiber is a promising reinforced fiber for CCL substrate of 5 G LTE.title-text